SURVEI KEPUASAN SISWA TERHADAP LAYANAN DI YAYASAN PENDIDIKAN ISLAM AL-QUDS SAMARINDA DENGAN SURVEI ANALISA SKALA LINKERT - Muhammad Nur; Ahmad Ridani; Muhammad Aulia Rahman (STKIP Subang, 2026)
This study aims to measure the level of student satisfaction with educational services at Yayasan Pendidikan Islam Al-Quds Samarinda using a survey method with Likert Scale analysis. Student satisfaction is considered an important indicator in evaluating the quality of educational services, which include aspects of teaching, facilities, administration, and staff services. The research employed a quantitative descriptive approach involving 30 randomly selected students from different educational levels. The research instrument was a closed questionnaire consisting of nine indicators: teaching quality, teachers’ ability to explain material, opportunities for discussion, quality of learning materials, main facilities, supporting facilities, administrative services, academic information, and staff friendliness. Data were analyzed using Likert scoring techniques and mean calculations for each indicator. The findings indicate that overall student satisfaction is in the “good” category. The highest score was found in staff friendliness (mean = 4.4), while aspects requiring improvement include supporting facilities (3.6), main facilities (3.8), opportunities for discussion (3.9), and academic information (3.9). These results show that the quality of educational services at Yayasan Pendidikan Islam Al-Quds Samarinda has generally been well implemented, although continuous improvements are needed, particularly in infrastructure, academic communication, and student participation in the learning process to achieve optimal satisfaction.